Editor & publisher international year book : the encyclopaedia of the newspaper industry (New York : Editor & Publisher, 1994)
"The encyclopedia of the newspaper industry."
Title from cover.
Pt. 2 of issues for 1995- called also: Who's where; pt. 1 of issues for 1999- published in two v., with Who's where as pt. 3.
Issued in parts, 1995-
Vols. for <2004-> issued in 3 pts: Pt.1: Dailies; Pt. 2: Weeklies (U.S. and Canada); Pt. 3: Contact directory (also called Who's where).
Vols. for <2004-> also called <84th ed.->
Issued 1920/21-1958 in Jan. as a regular number, or section of a regular number of: Editor & publisher.
Keywords: Newspapers -- Directories; Newspaper publishing -- Directories; Perswezen; NEWSPAPER PUBLISHING; DIRECTORIES; Newspaper publishing; Newspapers; Directories